Immunochip Meta-Analysis of Inflammatory Bowel Disease Identifies Three Novel Loci and Four Novel Associations in Previously Reported Loci. (31st March 2018) - Hong, Myunghee; Ye, Byong Duk; Yang, Suk-Kyun; Jung, Seulgi; Lee, Ho-Su; Kim, Byoung Mok; Lee, Soo Bin; Hong, Jeonghoon; Baek, Jiwon; Park, Sang Hyoung; Han, Buhm; Li, Yi; et al.
Abstract: Background and Aims: Recent meta-analysis of genome-wide association studies have identified over 241 inflammatory bowel disease susceptibility loci. However, the known variants only account for a fraction of inflammatory bowel disease heritability. To identify additional susceptibility loci, we performed a trans-ethnic meta-analysis as well as an Asian-specific meta-analysis, using all published Immunochip association results of inflammatory bowel disease. Methods: An inverse-variance fixed-effects meta-analysis was carried out across Korean and East Asian Immunochip datasets of 4156 cases and 4904 controls [Asian ancestry]. A trans-ethnic meta-analysis of inflammatory bowel disease was performed together with the European datasets of 38 155 cases and 48 485 controls genotyped on the immunochip using a Bayesian approach, Meta-Analysis of Trans-ethnic Association studies [MANTRA]. Results: We identified seven novel associations, including three novel susceptibility loci at MYO10-BASP1, PPP2R3C/KIAA0391/PSMA6/NFKB1A and LRRK1 as well as four novel secondary associations within previously known loci at NCF4, TSPAN32, CIITA and VANGL2 . The new loci further implicate alterations in B cell biology in Crohn's disease pathogenesis. The effects of five loci were universal across European and Asian ancestries, whereas the NCF4 and CIITA loci showed significant heterogeneity between European and East Asian populations. In addition, 103 previously known IBD loci showed supporting evidence of association with nominal significance [ p < 0.05] in Asians. Conclusions: Our findings of new loci not previously associated with IBD support the importance of studying inflammatory bowel disease genetics in diverse populations.